PANTUN DAN PEPATAH-PETITIH MINANGKABAU BERLEKSIKON FLORA DAN FAUNA - Rona Almos; Pramono Pramono; Reniwati Reniwati (Adabiyyāt: Jurnal Bahasa dan Sastra, 2014)
Pepatah-petitih is Minangkabau proverbs which contains advices and teachings from the elders. Every sentence found in Minangkabau proverbs contains the Minangkabau basic philosophy which is originally derived from the nature. The thought of Minangkabau people is based on natural phenomena. Minangkabau people learn from everyday life environment. Sometimes the Minangkabau proverbs are presented in form of poetry. Poetry is the most important kind of Minangkabau literature. It becomes a topic, kaba flowers, and ornate speech. Those poems and proverbs are Minangkabau traditional community knowledge (local genius) in the past. This article aims to describe the whole Minangkabau proverbs which contain the terms of flora and fauna and to explain the meaning of those proverbs. There are many terms of flora and fauna found in the proverbs of Minangkabau. The contents taught us in doing good, patience, pituah, perseverance, and truth. They contain rules and high values for the benefit of Minangkabau society.